Solitary Cecal Diverticulitis: An Unusual Cause of Acute Right Iliac Fossa Pain—A Case Report and Review of the Literature - Nikolaos Mudatsakis; Marinos Nikolaou; Konstantinos Krithinakis; Michail Matalliotakis; Nikolaos Politis; Emmanouil Andreadakis (Case Reports in Surgery)
Solitary cecal diverticulitis is a rare cause of acute abdominal pain in the Western world. Its clinical presentation, in most cases, mimics acute appendicitis. A 38-year-old Caucasian man presented with acute abdomen and clinical signs of acute appendicitis. Laparotomy was performed and revealed an inflammatory, solitary diverticulum of the cecum. A typical appendectomy was performed and a catheter was inserted for draining percutaneously the inflamed diverticulum of the cecum. The patient had an uneventful recovery and was discharged on the 4th postoperative day. This frequently misdiagnosed condition, in most cases, is being suspected and identified intraoperatively as acute appendicitis. The aim of this study is to review the available different surgical management options and to present an alternative therapeutic approach that may be valuable under specific circumstances.